Riots, Foster Homes and a Royal Wedding: The Unequal Allocation of Vulnerability in Kit de Waal's My Name Is Leon - Flores-Quesada, María Magdalena (My University, 2022)
Kit de Waal’s debut novel, My Name Is Leon (2016), was an instant success. Both critics and readers praised de Waal’s ability to capture the social complexities of Britain in the 1980s, a moment largely marked both by the royal wedding of Princess Diana and Prince Charles, and by the Handsworth race riots of 1981. The novel centres on Leon, a mixed-race nine-year-old boy that struggles in the British foster care system while his half-brother, Jake, a white and blue-eyed baby, is soon adopted. In this paper, I claim that de Waal manages to capture the unequal allocation of vulnerability in today’s societies. As such, vulnerability does not simply become more evident in particular groups, but it also evinces how the private and the public spheres become intertwined. Thus, the racism that Leon suffers in the foster care system extends to that found in the riots. The poverty that surrounds Leon’s circle contrasts with the wealth that the preparations for the royal wedding involve. By applying Robert E. Goodin’s “vulnerability model” (12) and Judith Butler’s understanding of vulnerability, I analyse the unequal allocation of responsibility and care in the novel. Goodin’s model demonstrates that the care for the other should extend outside the realm of family and friends, whereas Judith Butler’s analysis of vulnerability connects the notion with personal and collective resistance and resilience. I show how Leon’s sense of identity, belonging, and his personal relationships are shaped by a multilayered vulnerability. With my analysis, I demonstrate how Leon achieves to use this vulnerability as a transformative and empowering characteristic. As such, I argue that this novel is not only a tender bildungsroman told through a child’s perspective, but also, an effective denouncement of the unequal distribution of vulnerability in the public sphere that calls for a reorientation of our gaze towards the vulnerable other.
Keywords: Literatura contemporánea; Teoría crítica; Vulnerability; British fiction; Ethics of care